2016
DOI: 10.1080/09540121.2016.1200712
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age on care pathways of people living with HIV followed up in hospital

Abstract: The aging population of people living with human immunodeficiency virus (HIV) (PLWH) is exposed to a widening spectrum of non-AIDS-defining diseases. Thus, our objective was to compare the health care offered to PLWH according to age. We conducted a multicenter cross-sectional study on PLWH who consulted at one of 59 French HIV reference centers from 15th to 19th October 2012. Using our survey questionnaires, PLWH self-reported the medical care they received, whether or not tied to HIV infection monitoring, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…However, they seem to present more numerous comorbidities than those previously reported. 1,7 Though, as we noted in the present study, our self-questionnaire focused more closely on "disorders" than on identified organ diseases. Nevertheless, the HIV Outpatient Study deleterious interactions with ARVs.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…However, they seem to present more numerous comorbidities than those previously reported. 1,7 Though, as we noted in the present study, our self-questionnaire focused more closely on "disorders" than on identified organ diseases. Nevertheless, the HIV Outpatient Study deleterious interactions with ARVs.…”
Section: Discussionmentioning
confidence: 56%
“…6 This is especially important because after the infection stabilizes, a current care pathway only require bi-annual or annual hospital consultations where an ARV prescription is given for the following 6 months, or year. 7 During this 6-month or 12-month period, the pharmacist (hospital pharmacist or community pharmacist, according to the patient's preference) is often the only health professional a PLHIV will meet monthly, and who must ensure adherence to the treatment regimen. Another major challenge for the pharmacist can be patient therapeutic education (PTE) in conjunction with the various actors involved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study has some limitations; some comorbidities may have been underestimated because of a non declaration in the patient’s medical chart. However results of a recent French study evaluating comorbidities in HIV patients over 60 years find similar prevalence of the major comorbidities (cardiovascular diseases 30%, hypertension 27% and diabetes 15%) [ 35 ]. Furthermore individuals who died before Dec 31, 2015 were not included in the study and this does not allow to evaluate the frequency and reasons of death in this aging population.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidities, especially chronic renal disease and cardiovascular diseases, are becoming increasingly determinant in aging PLHIV, with a prognostic role that is as important as HIV-related prognostic factors such as CD4 cell count [ 14 ]. The burden of comorbidities is high in this population, and will continue to increase in the future [ 6 , 15 ]. This different epidemiology with lifestyle confounders and higher comorbidity burden suggests that a specific score to estimate mortality risk, specifically designed for aged PLHIV, and including HIV-related factors and comorbidities, would be of major clinical and research interest [ 2 , 7 ].…”
Section: Introductionmentioning
confidence: 99%